Bundle branch reentrant tachycardia treated with cardiac resynchronization therapy in a patient with dilated cardiomyopathy - Panagiotis Koudounis (Heart Vessels and Transplantation, 2019)
A 66 years old woman with known dilated cardiomyopathy and severely reduced ejection fraction presented with bundle branch reentrant tachycardia. Bundle branch reentrant tachycardia is an uncommon form of ventricular tachycardia incorporating both bundle branches into the reentry circuit. The diagnosis is based on electrophysiological findings and pacing maneuvres that prove participation of the His- Purkinje system in the tachycardia mechanism. Radiofrequency ablation of right bundle is proposed as the first line therapy. In our patient, the ablation imposed a high risk of complications in view of the existing conduction defects. We decided to proceed with a CRT – D implantation, which improved patient’s symptoms and diminished ventricular tachycardia episodes. As a result, biventricular pacing may serve as an alternative method to ablation treatment.